Research Needs and Priorities for Conservation of Indian Medicinal Flora - Biswas, S.A.S.; Jain, S. S.; Pal, Mohinder (Indian Forester, 2003)
South-East Asia, Africa, Latin America and Eastern Europe provide nearly 90 per cent of raw materials for medicinal exploitation. It is revealed that there are actually 121 plants tliat yielded prescription drugs as a result of the study on 35,000 species of plants. About 5,000 species world over are considered to have been examined throughly for the active principles. Only 41 species generate commercial sales to the tune of US$ 40 billion per year with nonformulation drugs as adjuncts claiming nearly US$ 60 billion. The Indian region endowed with nearly 20,000 species of plants highlight 75 major species of medicinal flora, out of which at least 25 were most sought after during the last decade. Nearly 3600 species of documented medicinal flora 540 find major use as herbal drugs (about 200 of these are used in bulk quantities and are of commercial potential). The families of plants such as Apocynaceae, Celastraceae, Compositae (Asteraceae), Simaroubaceae, Rutaceae, Thymelaeaceae, Magnoliaceae, Annonaceae, Boraginaceae, Leguminosae (Fabaceae), Liliaceae, Rubiaceae, Gymnosperms (Cephalotaxaceae) have anti-cancer drug yielding species. The paper provides botanical-cumphytogeographical regions of the country with specific elements of medicinal flora. The need for categorizing the rare and threatened medicinal and aromatic flora as per IUCN Red Data enlisting norms has been emphasized in the paper. Research need and priorities targeting different activities on the aspects of (i) Inventorization and Characterization, (ii) Monitoring and Assessment, (iii) Ex-situ Conservation, (iv) In-situ Conservation and (v) Utilization have been outlined in the paper.